Recurrence of Large-Vessel Vasculitis Induced by Multiple Types of Granulocyte Colony-Stimulating Factor Preparation in Patient with Large-Cell Neuroendocrine Lung Carcinoma: A Case Report - Yurie Seto; Tadaaki Yamada; Masashi Egami; Takumi Sugimoto; Izumi Sato; Satomi Tanaka; Yusuke Chihara; Kenji Morimoto; Masahiro Iwasaku; Shinsaku Tokuda; Yoshiko Kaneko; Koichi Takayama (Case Reports in Oncology, 2023)
With the increased use of granulocyte colony-stimulating factor (G-CSF) preparations, there is concern about the increase in G-CSF-associated large-vessel vasculitis; however, there have been no previous reports of vasculitis caused by multiple types of G-CSF preparations. We experienced a case of drug-induced large-vessel vasculitis caused by two different G-CSF products, which was difficult to diagnose. When treating patients with a history of large-vessel vasculitis caused by pegfilgrastim, we need to pay attention to its recurrence when using other G-CSF preparations.